2020
DOI: 10.1038/s12276-020-0427-8
|View full text |Cite
|
Sign up to set email alerts
|

Spi-C positively regulates RANKL-mediated osteoclast differentiation and function

Abstract: Spi-C is an SPI-group erythroblast transformation-specific domain transcription factor expressed during B-cell development. Here, we report that Spi-C is a novel receptor activator of nuclear factor-κB ligand (RANKL)-inducible protein that positively regulates RANKL-mediated osteoclast differentiation and function. Knockdown of Spi-C decreased the expression of RANKL-induced nuclear factor of activated T-cells, cytoplasmic 1, receptor activator of nuclear factor-κB (RANK), and tartrate-resistant acid phosphata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Spic, a PU.1-related TF, controls the development of red pulp macrophages ( Kohyama et al, 2009 ), B cells ( Laramee et al, 2020 ), and osteoclasts ( Go et al, 2020 ), partially by upregulation of adhesion genes such as integrin αM and αD ( Haldar et al, 2014 ; Okreglicka et al, 2021 ). Deletion of EP3 caused functional defects in adhesion and cytolysis in DP NK cells through reducing the activity of Spic, which also interrupts development of NK cells ( Kohyama et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spic, a PU.1-related TF, controls the development of red pulp macrophages ( Kohyama et al, 2009 ), B cells ( Laramee et al, 2020 ), and osteoclasts ( Go et al, 2020 ), partially by upregulation of adhesion genes such as integrin αM and αD ( Haldar et al, 2014 ; Okreglicka et al, 2021 ). Deletion of EP3 caused functional defects in adhesion and cytolysis in DP NK cells through reducing the activity of Spic, which also interrupts development of NK cells ( Kohyama et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nox-4 is a notable gene induced during the osteoclastogenesis process. The loss of Nox-4 activity halts the osteoclastogenesis process and favors the bone formation process [ 33 , 34 ]. The present observation of lowered Nox-4 expression demonstrated that the total osteoclastogenesis process was suspended in GTE supplemented OVX rats.…”
Section: Discussionmentioning
confidence: 99%
“…The next day, the wells were aspirated and replenished with media containing RANKL; this was repeated for the next 2 days. On day 10, the wells were aspirated and the bone chips were fixed and stained, as reported previously [ 49 ].…”
Section: Methodsmentioning
confidence: 99%